Analysis of Multiaxial Tensile Stresses in Cold Forging Tools - Killmann, Martin; Merklein, Marion (Lecture Notes in Mechanical Engineering, 2024)
Tools have a key role in cold forging as they directly influence part quality and process economics. High loads from the contact pressure exhibited by the workpiece are a major challenge regarding tool life. In complex geometries, tensile die stresses are concentrated in local areas and oriented both in axial and tangential directions. This superposition of loads leads to fatigue failure at the stress peaks. Since the interactions of multidirectional tensile stresses in cold forging tools have not been investigated in previous investigations, this paper aims to better understand the formation of local stress concentrations in axial and tensile directions as well as the possibilities to influence them. As tool loads in critical areas are difficult to measure during the process, simulation plays an important role in the evaluation of die stresses. Therefore, a model process with multiaxial tool stresses is simulated and the simulation results are compared to experimental values in order to validate the model. The simulation is then used to analyse the die load depending on the prestressing system.
CRIS-Team Scopus Importer:2024-09-13
Keywords: Cold forming; Die; Stress